CLINICAL PHARMACOLOGICAL APPROACH TO THE USE OF NONSTEROIDAL DRUGS IN CHILDREN (World Bulletin of Public Health, 2024)
The article discusses the mechanisms of action, various effects of nonsteroidal anti-inflammatory drugs, a consensus view on the risks of developing induced damage to the upper and lower gastrointestinal tract, as well as ways to overcome them. Drugs with relatively little side effect on the gastrointestinal tract are characterized.